ANALISIS KELAYAKAN INVESTASI ANGKUTAN PARIWISATA DI PROPINSI BALI - Cok Putra Wirasutama; P. Alit Suthanaya; D. M. Priyantha Wedagama (JURNAL SPEKTRAN, 2015)
Abstract : Tourism is the main sector to increase the economy of Province of Bali. A lot of components involved in this tourism industry such as hotel, restaurant, and other tourism objects. The function of tourism transportation is to connect those places. The objective of this study is to analyze the investment feasibility on the torusim transportation in the Province of Bali.   Analysis was performed on PT Gd Bali Transport and PT Amanda Legian Tours using interest rate at 15% and investment duration for 7 years. The outcome for PT Gd Bali Transport was the value of NPV Rp.(-) 11.866.640.000, IRR uncountable, BCR : 0,37 and PBP 21 years. While for PT Amanda Legian Tours was NPV Rp.(-) 875.310.000, IRR uncountable, BCR : 0,77 and PBP 9 years. That outcome indicating that tourism transportation in the Province of Bali was not financially feasible.